Research Trends in the Field of Participatory Governance: Drawing a Map of Co-occurrence and Co-word Analysis - Seyed Mohsen Mirbagheri; Seyed Mostafa Jalili (مدیریت دولتی)
Objective In today's dynamic societal structure, the active participation and involvement of people in decision-making, implementation, and monitoring processes are indispensable for the successful realization of any plan. The concept of participatory governance, central to the success of political and administrative systems, necessitates a comprehensive review of scientific publications in this domain. Experts in participatory governance face the daunting task of navigating through an extensive array of research documents to analyze the field's various strengths and weaknesses. This task, though crucial, is arduous and time-consuming given the sheer volume of literature available. Therefore, the utilization of scientific support tools to unearth and understand the conceptual framework of this area is both invaluable and necessary. The primary aim of this article is to address fundamental questions pertaining to scientific productions in participatory governance, a field increasingly recognized as vital in diverse scientific disciplines, particularly in political and governmental management. This evaluation is conducted using Co-word Analysis, a method that reveals the conceptual dynamics within the field. Methods The study embarks on an analytical journey through scientific productions in the domain of participatory governance spanning from 1999 to 2023, utilizing the Web of Science database as a reference point. To process and analyze the data, the study employs VOSviewer and Excel software, tools adept at illustrating the distribution of publications across different countries and their prevalence in various journals. This extensive examination encompasses 35,800 scientific documents, leading to the extraction of 70,771 keywords, each offering insight into the evolving landscape of participatory governance research.